Science Rewritten to Accommodate its Origin - Deans, Michael T (International Journal of Innovative Research in Medical Science, 2016)
A ferroelectric phase transition in ice at ~72 K releases latent energy as λ ~ 4 μ infrared laser light, ‘ice light’, energizing selected targets. Polarized by multiple reflection[22], it photophosphorylated deoxynucleotides, turning tropical waters into a noodle soup of chiral DNA. tRNA analogues ‘transport DNAs’, tDNAs embedded in Alexander Oparin’s lightning-charged coacervates[23] formed H-bond lined pores. Absorbed ice light created an electric field, driving a ratchet mechanism which actively imported charged carrier-substrate complexes. All life descends from the first cell to replicate a tDNA and depends on the trace element requirements of 64 tDNA variants. They constitute life’s atomic alphabet, their substrate complexes its molecular vocabulary. The inviolable rules of active transport predate protein synthesis and enzyme catalysis. Medical, veterinary and pharmaceutical data are consistent with nine independent metabolic pathways. My account of water transport contradicts Peter Mitchell’s chemiosmotic hypothesis.[24] Trace element deficiencies disabling active transport cause most mental and physical maladies, supplements could prevent them. ‘Differentiation DNAs’, dDNAs selecting tDNAs control cells’ substrate uptake, c.f. mRNAs encode protein synthesis by selecting tRNAs. Barrels of α-helices[25] supplement tDNAs and tDNA genetics governs familial inheritance of metabolic disorders, a minion-based data base would facilitate their diagnosis. Trace element supplements would prevent heart attacks, strokes, cancers, diabetes, Alzheimer’s dementia and rarer conditions, improve health and reduce NHS expenditure. The 189*18 arrays of proton ordered H-bonds connecting amino acid ω-amines to DNA phosphates on ‘minions’ control metabolism, serve as biological clocks, memory stores and personality biased brain chips and are basis for reinterpreting scientific dogma. Nine parallel metabolic pathways reflecting their 9-fold symmetry control metabolism. Oscillating H-bonds accelerate protons along minion tunnels, driving molecular scale nuclear fusion. Trapping the γ-rays released at source could solve current energy and pollution crises. Computers and data-bases modelled on minions promise human-friendly artificial intelligence satisfying Turing’s criteria.[26] Comparing cybernetics, psychology and traditional wisdom suggested ‘minions’, the name connotes subservience. They comprise 189 anti-parallel β-sheet hairpins[27] with alternate neutral and basic amino acid residues and proline forming an asymmetric U-bend. They hold nine DNA base pairs flat, forming a nine-coil abacus. Evolved to pack DNA on chromosomes for efficient replication, they underpin philosophy and science, account for human intelligence and resolve many questions. My mutually consistent arguments contradict accepted dogma.